Temperature and Composition Dependent Optical Properties of CdSe/CdS Dot/Rod‐Based Aerogel Networks. Issue 2 (23rd November 2021) - Rusch, Pascal; Pluta, Denis; Lübkemann, Franziska; Dorfs, Dirk; Zámbó, Dániel; Bigall, Nadja C.
Abstract: Employing nanocrystals (NCs) as building blocks of porous aerogel network structures allows the conversion of NC materials into macroscopic solid structures while conserving their unique nanoscopic properties. Understanding the interplay of the network formation and its influence on these properties like size‐dependent emission is a key to apply techniques for the fabrication of novel nanocrystal aerogels. In this work, CdSe/CdS dot/rod NCs possessing two different CdSe core sizes were synthesized and converted into porous aerogel network structures. Temperature‐dependent steady‐state and time‐resolved photoluminescence measurements were performed to expand the understanding of the optical and electronic properties of these network structures generated from these two different building blocks and correlate their optical with the structural properties. These investigations reveal the influence of network formation and aerogel production on the network‐forming nanocrystals. Based on the two investigated NC building blocks and their aerogel networks, mixed network structures with various ratios of the two building blocks were produced and likewise optically characterized. Since the different building blocks show diverse optical response, this technique presents a straightforward way to color‐tune the resulting networks simply by choosing the building block ratio in connection with their quantum yield. Abstract : Aerogel networks based on CdSe/CdS dot/rod nanoparticles with different core sizes and consequently different emission colors are reported. The optical properties of such networks are investigated with regards to the influence of temperature down to cryogenic temperatures and the influence of the mixing of two different color dot/rod building blocks.